Pharmacy Education in Jordan, Saudi Arabia, and Kuwait - Al-Wazaify, Mayyada (American Journal of Pharmaceutical Education, 2006)
The practice of pharmacy, as well as pharmacy education, varies significantly throughout the world. In Jordan, Kuwait, and Saudi Arabia, the profession of pharmacy appears to be on the ascendance. This is demonstrated by an increase in the number of pharmacy schools and the number of pharmacy graduates from pharmacy programs. One of the reasons pharmacy is on the ascendance in these countries is government commitment to fund and support competitive, well-run pharmacy programs. In this report we describe pharmacy education in 3 Middle East countries: Jordan, Kuwait, and Saudi Arabia. All 3 countries offer bachelor of pharmacy (BPharm) degrees. In addition, 2 universities in Jordan and 1 in Saudi Arabia offer PharmD degree programs. The teaching methods in all 3 countries combine traditional didactic lecturing and problem-based learning. Faculties of pharmacy in all 3 countries are well staffed and offer competitive remuneration. All 3 countries have a policy of providing scholarships to local students for postgraduate training abroad. The majority of students in Jordan and Kuwait are female, while the ratio of male to female students in Saudi Arabia is even. Students’ attitudes towards learning are generally positive in all 3 countries. In Saudi Arabia and Kuwait, most pharmacy graduates work in the public sector, while in Jordan, the majority work in the private sector.